Analisis Dampak Perubahan Status BPJS Non-Aktif Menjadi Program Universal Health Coverage (UHC) Guna Meningkatkan Mutu Pelayanan di Rumah Sakit - Ai Susi Susanti; Nur Afni Salsa Billa (HB PRESS, 2025)
The Universal Health Coverage (UHC) program is a strategic initiative by the Indonesian government to ensure that all citizens have access to quality healthcare services without financial barriers. This study aims to analyze the causes behind the inactive status of BPJS (Indonesia’s national health insurance) participants, evaluate the effectiveness of UHC implementation in addressing access challenges, and examine its impact on the quality of healthcare services. A descriptive qualitative method was employed through a case study at a hospital in Bandung that has implemented the UHC program. Informants included BPJS administrative officers, healthcare workers, and patients who transitioned from inactive BPJS status to UHC participants. Data were collected through in-depth interviews, direct observation, and document analysis. The results showed that out of 173 applications, 89.6% of previously inactive BPJS participants were successfully enrolled in the UHC program. This policy had a positive impact, improving healthcare accessibility, service efficiency, and patient satisfaction. However, administrative and data validation issues were the main obstacles. These findings indicate that UHC is effective in expanding healthcare coverage, but it requires robust data systems and active local government support for policy alignment and funding.